OPTIMUM DESIGN OF NONLINEAR STEEL SPACE FRAMES VIA TABU SEARCH METHOD - Degertekin, S. Ozgur; Hayalioglu, M. Sedat; Ulker, Mehmet (Yildiz Technical Univ, 2006)
In this study, an algorithm and its computer program were developed for the optimum design of steel space frames using tabu search method. Two methods were followed and the results obtained from these methods were compared. Geometrical nonlinearity was considered and the material was assumed to be linear-elastic in the analysis of the space frames. The lateral and vertical loads, lateral displacement, interstory drift and stress constraints imposed on the frames were taken from the relevant design codes. Moreover, section size constraints was considered in the optimum design. In this study, obtaining of minimum-weight frames was aimed under the above mentioned loads and constraints. Optimization methods have to be suitable for employing discrete design variables because of using standard steel sections in the design of steel frames. Tabu search is suitable optimization method for using discrete design variables. Optimum designs of two steel space frame were performed to show the applications of the developed algorithms and computer programs.
Keywords: Steel space frames; nonlinear analysis; optimum design; tabu search